THE DEVELOPMENT OF ICT COMPETENCIES OF PEDAGOGICAL WORKERS - DOSTAL, Jiri (Trends in education, 2010)
This paper presents the partial results of the project CZ.1.07/1.3.13/01.0044 ``The development of ICT competencies of pedagogical workers from Olomouc region with use of e-Learning''. This project is co-financed by the European social fund EU and the state budget of the Czech Republic.
Keywords: education; technology education; innovation.